Implementation evaluation of a collective impact initiative to promote adolescent health in Oklahoma County, USA - Whitney R. Garney; Sonya Panjwani; Kelly Wilson; Kristen E. Garcia; Sharayah Fore; Shelby C. Lautner; Laura Lang; Brittney Criswell; Ronneal Mathews (BMC, 2022)
Abstract Background The teenage birth rate in the USA has considerably decreased in recent decades; however, more innovative, collaborative approaches are needed to promote adolescent health and prevent teenage pregnancy at the community level. Despite literature on the promising results of the collective impact (CI) model for health promotion, there is limited literature on the model's ability to reduce teenage pregnancies in a community. The Central Oklahoma Teen Pregnancy Prevention Collaboration is applying the CI model to foster collaboration among multiple stakeholders with the goal of increasing community and organizational capacity to improve adolescent health outcomes. This paper reports the findings from the initiative's implementation evaluation, which sought to understand whether the CI model improved collaboration among organizations and understand barriers and facilitators that affected program delivery. Methods Program implementers and evaluators jointly developed research questions to guide the intervention and evaluation design. The Consolidated Framework for Implementation Research (CFIR) was used to assess program components including the intervention characteristics, organization setting, community setting, facilitator characteristics, and the process of implementation. Primary sources of data included performance measures, meeting observations (n = 11), and semi-structured interviews (n = 10). The data was thematically analyzed using CFIR constructs, community capacity domains, and the five constructs of CI. Results Key findings include the need for shortened meeting times for meaningful engagement, opportunities for organizations to take on more active roles in the Collaboration, and enhanced community context expertise (i.e., those with lived experience) in all Collaboration initiatives. We identified additional elements to the core constructs of CI that are necessary for successful implementation: distinct role identification for partner organizations and incorporation of equity and inclusivity into collaboration processes and procedures. Conclusions Results from this implementation evaluation provide valuable insights into implementation fidelity, participant experience, and implementation reach of an innovative, systems-level program. Findings demonstrate the context and requirements needed to successfully implement this innovative program approach and CI overall. Additional core elements for CI are identified and contribute to the growing body of literature on successful CI initiatives.